COVID-19 pandemic and its impact on service provision: A cardiology prospect. Issue 8 (10th November 2021) - Adam, Sana; Zahra, Syeda Anum; Chor, Cheryl Yan Ting; Khare, Yuti; Harky, Amer
Abstract: Coronavirus disease 2019 (COVID-19) pandemic has significantly impacted the availability of cardiology services and management of cardiac conditions. Elective surgeries, outpatient appointments and cardiac imaging have been largely cancelled across the world due to the risk of infection transmission and the need for reallocation of resources to deal with the increasing number of COVID-19 patients. The impact on patients with cardiac co-morbidities during these times may be drastic. However, cardiologists and hospitals across the world have implemented measures to ensure on-going monitoring and care of patients remotely. In this review, we discuss the impact of COVID-19 on cardiac services including interventional cardiology services, cardiac imaging and outpatient appointments. In addition, implications for future research and clinical practice are also discussed.